Is there a relationship between HMGB1 levels and clinical conditions of patients tested positive for COVID-19? - Nevhiz Gundogdu; Mustafa Tanriverdi; Hale Celikturk; Mustafa Yildirim; Necla Benlier; Hanifi Ayhan Ozkur; Hulya Cicek (Medicine Science, 2022)
Severe COVID-19 may be complicated by acute respiratory distress syndrome, sepsis and septic shock, which can lead to death. These life-threatening conditions are supposed to be the outcome of immune system overactivity, which causes cytokine storm syndrome and multiple organ failure. High mobility group box-1 (HMGB1) is one of the damages associated with molecular model molecules (DAMPs), which plays a role in the pathogenesis of various inflammatory diseases and infections where many studies have been conducted. In this study, the role of HMGB1 in COVID-19 positive cases, which could be considered a potential diagnosis and treatment method, is investigated. COVID-19 patients, who were hospitalized to our clinic in Sanko University Hospital, were included in this study. Blood samples were taken from patients to measure their HMGB1 level which was then compared with their clinical severity. It is observed that HMGB1 levels rise in COVID-19 patients when compared to the control group, but the severity of the illness does not get particularly affected by their HMGB1 levels. [Med-Science 2022; 11(4.000): 1398-401]